2023
DOI: 10.1038/s41419-023-06300-2
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib induces ferroptosis in gastrointestinal stromal tumors by promoting STUB1-mediated GPX4 ubiquitination

Xiangfei Sun,
Qiang Zhang,
Xiaohan Lin
et al.

Abstract: Imatinib (IM) has significantly improved the prognosis of gastrointestinal stromal tumor (GIST) patients, but some patients still have primary resistance to IM, and approximately half of patients develop acquired drug resistance within 2 years of treatment, necessitating exploration of new treatment strategies. Targeting ferroptosis as a novel approach to tumor treatment has gained attention. Yet, there is limited research on ferroptosis in GIST, and the underlying mechanism remains unclear. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…GPX4, a selective protein glutathione peroxidase, degrades hydroperoxides and reduces the production of lipid peroxidation that damaged membranes. It also inhibited PUFA-OOH production of PUFA–OH and GSH production of GSSG in cells . The study showed that alcohol significantly reduced GPX4 expression and GSH content.…”
Section: Discussionmentioning
confidence: 99%
“…GPX4, a selective protein glutathione peroxidase, degrades hydroperoxides and reduces the production of lipid peroxidation that damaged membranes. It also inhibited PUFA-OOH production of PUFA–OH and GSH production of GSSG in cells . The study showed that alcohol significantly reduced GPX4 expression and GSH content.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding breast cancer, doxorubicin-induced cardiotoxicity may involve iron-dependent processes and oxidative stress, prompting co-administration with iron chelators to adjust iron levels and potentially induce ferroptosis [129]. In gastrointestinal stromal tumors, Imatinib has been found to induce ferroptosis through STUB1-mediated GPX4 ubiquitination [130]. In a prior study, we observed that cetuximab, an approved treatment for metastatic CRC with KRAS, enhanced RSL3-induced ferroptosis by suppressing the NRF2/HO-1 pathway in KRAS-mutant CRC [131].…”
Section: Ferroptosis As a Novel Approachmentioning
confidence: 99%
“…Mechanistically, they demonstrated that STUB1 promoted polyubiquitination of GPX4 on lysine 191, leading to its degradation by the ubiquitin proteasome pathway. They finally showed that the combination of RSL3, a ferroptosis inducer with Imatinib synergistically inhibited GIST cell proliferation [ 47 ].…”
Section: Targeting Gpx4 and Ferroptosis In Amlmentioning
confidence: 99%